Pass-Through of Own and Rival Cost Shocks: Evidence from the U.S. Fracking Boom - Muehlegger, Erich; Sweeney, Richard L. (The Review of Economics and Statistics, 2022)
Abstract In imperfectly competitive settings, a firm's price depends on its own costs as well as those of its competitors. We demonstrate that this has important implications for the estimation and interpretation of pass-through. Leveraging a large input cost shock resulting from the fracking boom, we isolate price responses to firm-specific, regional, and industry-wide input cost shocks in the U.S. oil refining industry. The pass-through of these components varies from near zero to full pass-through, reconciling seemingly disparate results from the literature. We illustrate the policy implications of rival cost pass-through in the context of a tax on refinery carbon emissions.